2022
DOI: 10.1063/5.0088772
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic cavity shear layer control using spanwise pulsed spark discharge array

Abstract: An experimental study on supersonic cavity flow control using a spanwise pulsed spark discharge array (SP-PSDA) is performed in this paper. High speed schlieren imaging at a frame rate of 50 kHz is deployed for flow visualization. The schlieren snapshots, as well as their statistics, are analyzed to reveal the supersonic cavity flow control effect and its underlying mechanism. Results show that the shear layer presents a wave-like oscillation due to thermal bulbs induced by SP-PSDA. Specifically, the shear lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Two types of nanosecond-pulsed actuators are commonly adopted in experimental research, namely, the nanosecond spark discharge actuator and the nanosecond-pulsed surface dielectric barrier discharge (NS-SDBD) actuator [5,6], which show similar effects for supersonic flow control. Studies have shown that nanosecond discharge is able to control detached shockwaves [7] and increase the instability of the cavity shear layer in supersonic flow [8], proving the feasibility of this actuation method.…”
Section: Introductionmentioning
confidence: 96%
“…Two types of nanosecond-pulsed actuators are commonly adopted in experimental research, namely, the nanosecond spark discharge actuator and the nanosecond-pulsed surface dielectric barrier discharge (NS-SDBD) actuator [5,6], which show similar effects for supersonic flow control. Studies have shown that nanosecond discharge is able to control detached shockwaves [7] and increase the instability of the cavity shear layer in supersonic flow [8], proving the feasibility of this actuation method.…”
Section: Introductionmentioning
confidence: 96%